2021
DOI: 10.1155/2021/7913950
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Trichoderma Strains isolated from Natural Habitats in China with Potential Agricultural Applications

Abstract: Trichoderma spp. are widely distributed in natural habitats and have been evaluated as a potential biocontrol agent (BCA) for disease control and plant growth promotion. In this study, 1308 Trichoderma strains were obtained from the plant rhizosphere soil, above-ground plants, and decaying wood from natural habitats in China. Among them, 49 Trichoderma strains showed a good inhibitory effect, especially against Botrytis cinerea, Fusarium oxysporum, and Colletotrichum gloeosporioides with inhibition rate above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…The similar ndings were reported by Kumar et al (2012) who observed 12 isolates of Trichoderma in different locations of South Andaman with ITS region that were characterized, and the sequence analysis of these isolates identi ed 7 different species (T. harzianum, T. viride, T. brevicompactum, T. ovalisporum, T. erinaceum, T. asperellum and T. orientalis). The similar observations were supported by Xue et al (2021), Hoyos-Carvajal et al ( 2009) and Hermosa et al (2000). Trichoderma isolates of different bio-control capabilities were also characterized in three main clades with ITS sequence analysis as the ndings of Maymon et al (2004).…”
Section: Discussionsupporting
confidence: 73%
“…The similar ndings were reported by Kumar et al (2012) who observed 12 isolates of Trichoderma in different locations of South Andaman with ITS region that were characterized, and the sequence analysis of these isolates identi ed 7 different species (T. harzianum, T. viride, T. brevicompactum, T. ovalisporum, T. erinaceum, T. asperellum and T. orientalis). The similar observations were supported by Xue et al (2021), Hoyos-Carvajal et al ( 2009) and Hermosa et al (2000). Trichoderma isolates of different bio-control capabilities were also characterized in three main clades with ITS sequence analysis as the ndings of Maymon et al (2004).…”
Section: Discussionsupporting
confidence: 73%
“…In a seedling growth assay, rice ( Oryza sativa ) was used to demonstrate the growth-promoting potential of biosustained Trichoderma strains in greenhouse conditions ( Abuhena et al, 2022b ; Xue et al, 2021 ). After washing with autoclaved water (1–2 times), the seeds were disinfected by dipping in 75% ethanol (1 min), followed by dipping in 0.5% sodium hypochlorite (5 min), and finally washing 5 times with autoclaved water.…”
Section: Methodsmentioning
confidence: 99%
“…In order to evaluate the antagonistic effect of Trichoderma strains, the confrontation of antagonistic isolates and pathogens is usually carried out using a double culture technique (Chen et al 2019;Degani et al 2023;Nagy et al 2023). The ability of Trichoderma strains to produce extracellular enzymes such as protease, phosphatase, cellulase, chitinase and glucanase is most often assessed by colorimetric methods, using dinitrosalicylic acid (DNS) or chromogenic substrates to determine the amount of enzyme production (Go et al 2019;Mustafa et al 2020;Xue et al 2021). The most common method to evaluate auxin (indole-acetic acid) synthesis by Trichoderma strains is the Salkowski test (Abdenaceur et al 2022;Bader et al 2020;López 2023;Nagy et al 2023).…”
Section: Selection Of Trichoderma Strains For Microbial Inoculantsmentioning
confidence: 99%